Current volatility as a measure of market risk. (2017) - Kussy, Mikhail
The article offers the author's approach to the definition of market risk and specifies its differences from the economic and financial risks. The necessity of taking into account the social component in the analysis of market risk is shown. Two different types of market risk are identified. Convincingly, the article shows the inconsistency of the use of the existing methods for measuring volatility as a measure of market risk, as defined in the article. The article puts forward a new kind of market volatility, which is qualitatively different from the types of volatility considered in the article. By means of the Grassberger-Procaccia entropy, we prove that the measure of current volatility proposed by the author can be adequately used as a measure of market risk. The algorithms of the current volatility measure's use as a quantitative measure of market risk of both types are offered.